Effects of Oxygen Content on the Ablation Behavior of Silicone Rubber-Based Insulation Material - Yi-ang Shi; Bai-lin Zha; Qing-dong Su; Xu-dong Jia (International Journal of Aerospace Engineering)
A self-designed oxygen-kerosene ablation system was employed to research the ablation properties of silicone rubber-based insulation material under different oxygen-rich conditions, that is, 0%, 5.00%, 7.71%, 17.01%, and 18.50%. The morphology of posttest specimens was analyzed via a scanning electron microscope (SEM), and the ablation rates were calculated. Experimental results showed that when the particle concentration was a fixed value, the mass and the linear ablation rates increased first and then decreased with the rise of oxygen content; the maximum values were 0.572 g/s and 0.933 mm/s, respectively. Under high oxygen-rich conditions, the formation of silicone rubber restricted the further increase of the ablation rates, filling more gaps of the reaction layer with liquid silicone rubber. Meanwhile, the thickness of the liquid glass layer attached to the surface was increased, which acted as a buffer against the impacts and erosion of particles and retarded the consumption and recession of materials. Excess oxygen spread to the edge of the ablation pit and reacted. Finally, these led to the increase in diameter of the ablation pit and the decrease of two types of ablation rates.